The Documentary Remains of the Perpetrator: Images and Texts - Cárcel Ejarque, Irene; Monsell Corts, Juanjo (THÉMATA. Revista de Filosofía, 2022)
A tendency to approach the past from the interpretative framework of memory at the expense of the classical historiographical approach emerged during the last decade of the 20th century in Western societies. This phenomenon was called memory boom and its raison d’être was related, on the one hand, to the belated acceptance of the survival of traumatic memories in all the subjects involved in regimes or episodes of perpetration of mass violence.